The Influence of Molasses Concentration on the Physical and Mechanical Properties of Evaporation Boat Waste-Based Crucibles - Rusiyanto Rusiyanto,; Rahmat Doni Widodo,; Ares Yudi Prasetyo,; Deni Fajar Fitriyana,; Aldias Bahatmaka,; Sudiyono Sudiyono,; RIZKI SETIADI,; Wara Dyah Pita Rengga,; Rifky Ismail,; Athanasius Priharyoto Bayuseno,; Anjar Priyatmojo,; Wahyu Ramdhani,; et al. (International Journal of Integrated Engineering, 2024)
Crucibles are essential tools used in many industries, and their production can be resource-intensive and costly. This study aims to determine the potential of evaporation boat waste produced by the plastic metallization industry with molasses as a binder in crucible production. This study explores the effects of various concentrations of molasses on the mechanical and physical properties of crucibles made from evaporation boat waste. The evaporation boat waste used in this study was crushed and filtered with a 100-mesh sieve. Molasses were added during the mixing process with concentrations of 0 wt.%, 5 wt.%, 10 wt.%, 15 wt.%, and 20 wt.%. The mixing process was done for 120 minutes, followed by compaction with a pressure of 25 MPa. The green body formed is dried at 100?C for 300 minutes. In this study, firing was done at 1150?C temperature with 240 minutes of holding time. The specimens in this study were characterized using XRD, SEM, density, hardness, and 3-point bending tests. The results showed that the resulting crucible only had BN and TiB2 crystalline phases. Using molasses as a binder showed that crucible specimens did not form a new crystalline phase. Increasing the molasses content from 0 wt.% to 5 wt.% led to an increase in the physical and mechanical properties of the crucible specimens. However, the mechanical and physical properties of the crucible specimens decreased with the use of molasses that exceeded 5 wt.%. The best mechanical and physical properties of crucible specimens were produced using 5 wt.% molasses. This composition has a weight percentage of BN and TiB2 of 68.9% and 31.1%, with density, hardness, and flexural strength of 2.36 g/cm3, 64 HRA, and 31.5 MPa.